Analýza souboru pacientů s onemocnením vyvolaným toxinem Clostridium difficile hospitalizovaných na Klinice infeckcních chorob v Brne v letech 2007-2010 - Vojtilová, Lenka; Freibergerová, Michaela; Juránková, Jana; Husa, Petr; Polák, Pavel; Kocourková, Hana (Klinicka mikrobiologie a infekcni lekarstvi, 2011)
BACKGROUND: To describe a set of patients hospitalized at the Clinic of Infectious Diseases of the University Hospital Brno with Clostridium difficile infection (CDI), to interpret clinical and epidemiological data, and to determine the risk factors for the disease and its complications. MATERIAL AND METHODS: A retrospective study of 284 patients with confirmed diagnosis of Clostridium difficile infection hospitalized between 1 January 2007 and 31 December 2010. Epidemiological, clinical and laboratory data were collected from their clinical documentation. RESULTS: Of the 284 patients with a mean age of 73.2 years, 38.0 % were men. Risk factors for developing CDI include the use of antibiotics in the previous 8 weeks (89.1 % of patients), age over 65 years (77.6 %), hospitalization in the previous 4 weeks (65.5 %), and the use of proton pump inhibitors (41.9 %). Recurrence was noted in 89 (31.3 %) cases. Sixty-six (23.2 %) patients required intensive care and 50 (14.6 %) patients died during their hospitalization. Isolates of C. difficile from the stool of 4 patients were sent for ribotyping and identified as ribotype 176. CONCLUSIONS: The CDI rates at the clinic KICH have increased in the recent years. The rise is consistent with the global trends. The study confirmed the disease risk factors reported in the literature. The disease is associated with a high percentage of relapses and complications.
Keywords: recidiva; Humans; lidé středního věku; Female; rizikové faktory; Aged; dospělí; senioři; lidé; nekrotizující enterokolitida; antibakteriální látky; hospitalizace; Adult; ženské pohlaví; Anti-Bacterial Agents; Hospitalization; Male; Middle Aged; Enterocolitis, Necrotizing; Aged, 80 and over; Recurrence; senioři nad 80 let; mužské pohlaví; Clostridioides difficile; Risk Factors